2017
DOI: 10.1037/cep0000104
|View full text |Cite
|
Sign up to set email alerts
|

The smartphone and the driver’s cognitive workload: A comparison of Apple, Google, and Microsoft’s intelligent personal assistants.

Abstract: The goal of this research was to examine the impact of voice-based interactions using 3 different intelligent personal assistants (Apple's , Google's for Android phones, and Microsoft's ) on the cognitive workload of the driver. In 2 experiments using an instrumented vehicle on suburban roadways, we measured the cognitive workload of drivers when they used the voice-based features of each smartphone to place a call, select music, or send text messages. Cognitive workload was derived from primary task performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 24 publications
4
72
0
1
Order By: Relevance
“…In fact, many newer-model vehicles come equipped with voice-activated systems that allow drivers to adjust climate control, select music, place and receive phone calls, send and read textual messages, and interact with social media. The impact of these voice-based commands on the motorist’s cognitive workload is unknown; however, voice-command laboratory surrogates with perfect reliability have been shown to produce surprisingly high levels of workload (Strayer, Cooper, Turrill, Coleman, & Hopman, 2015a, Strayer et al, 2015b). Moreover, older adults are likely to have greater difficulty using these voice-based systems and, ironically, they are more likely to purchase new vehicles equipped with these features (Sivak, 2013).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, many newer-model vehicles come equipped with voice-activated systems that allow drivers to adjust climate control, select music, place and receive phone calls, send and read textual messages, and interact with social media. The impact of these voice-based commands on the motorist’s cognitive workload is unknown; however, voice-command laboratory surrogates with perfect reliability have been shown to produce surprisingly high levels of workload (Strayer, Cooper, Turrill, Coleman, & Hopman, 2015a, Strayer et al, 2015b). Moreover, older adults are likely to have greater difficulty using these voice-based systems and, ironically, they are more likely to purchase new vehicles equipped with these features (Sivak, 2013).…”
Section: Significancementioning
confidence: 99%
“…Our prior research provided a benchmark for the cognitive workload associated with common in-vehicle activities (Strayer et al, 2015a, 2015b; see also Cooper, Ingebretsen, & Strayer, 2014; and Strayer, Turrill, Coleman, Ortiz, & Cooper, 2014). In our studies, we developed and validated a cognitive distraction scale based on converging operations from the laboratory, driving simulator, and an instrumented vehicle driven in a residential section of Salt Lake City.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns have been raised about the cognitive demands of tasks that still remain with voice interfaces (Cooper, Ingebretsen, and Strayer 2014; Reimer, Mehler, McAnulty, et al 2013; Reimer et al 2010, 2012; Strayer et al 2013; Strayer 2015a, 2015b; Strayer et al 2014). At the same time, several studies have found that self-reported workload, physiological arousal (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Combined speech and gesture control is the current state of the art in many applications. Whereas gesture control primarily requires physical effort, speech control involves predominantly cognitive effort, as previously demonstrated with regard to the speech control of mobile phones during driving tasks [2]. In 2013, more than ten thousand industrial accidents involving fork lift trucks were reported in Germany, approximately one-third with fatal consequences [3].…”
Section: Introductionmentioning
confidence: 99%